A CONTRASTIVE ANALYSIS OF TRADITIONAL GRAMMAR TEACHING AND COMMUNICATIVE LANGUAGE TEACHING IN TEACHING ENGLISH GRAMMAR AND VOCABULARY - Çiftci, Harun; Özcan, Mehmet (International Online Journal of Education and Teaching, 2021)
This study aimed to compare whether TGTM or CLT was more effective in teaching English language grammar and vocabulary. The participants of this study were sixty-eight 9th grade students attending to a high school. Mixed methods research design was grounded comprising a pre-test and post-test quasi-experimental design. The results of the pre and post-tests, quizzes and the oral productions of the participants were analyzed based on error analysis. It was observed that the students, who were taught English grammar via TGTM made fewer errors than those who were taught via CLT in both their written and oral productions. Additionally, vocabulary production was higher for the students who were taught based on TGTM than those in CLT. As a result, the quantitative and qualitative findings of the study suggested that TGTM was more practicable and productive than CLT in teaching and learning English grammar and vocabulary.